1995
DOI: 10.1111/1523-1747.ep12606218
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines in Human Keratinocyte Differentiation

Abstract: Human keratinocytes have the capacity to synthesize catecholamines from L-tyrosine, which in turn is produced from L-phenylalanine via phenylalanine hydroxylase. This enzyme activity is controlled by the supply of the essential cofactor/electron donor (6R)5,6,7,8 tetrahydrobiopterin (6-BH4). Undifferentiated keratinocytes express high levels of the rate-limiting enzymes for the de novo synthesis of 6-BH4, i.e., GTP-cyclohydrolase-1, and for its recycling, i.e., 4a-hydroxytetrahydrobiopterin dehydratase. As a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 25 publications
6
97
0
1
Order By: Relevance
“…The skin also expresses epidermal equivalents of another bioamine-based system, the catecholaminergic systems ( 29,30 ). This also includes a 6-tetrahydrobiopterin (6BH 4 ) generating system ( 30,31 ), which acts as a co-factor for phenylalanine, tyrosine, and tryptophan hydroxylases.…”
Section: Cutaneous Pathway For Melatonin Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The skin also expresses epidermal equivalents of another bioamine-based system, the catecholaminergic systems ( 29,30 ). This also includes a 6-tetrahydrobiopterin (6BH 4 ) generating system ( 30,31 ), which acts as a co-factor for phenylalanine, tyrosine, and tryptophan hydroxylases.…”
Section: Cutaneous Pathway For Melatonin Synthesismentioning
confidence: 99%
“…This also includes a 6-tetrahydrobiopterin (6BH 4 ) generating system ( 30,31 ), which acts as a co-factor for phenylalanine, tyrosine, and tryptophan hydroxylases. Expression and activity of aromatic amino acid decarboxylase (AAD) has also been demonstrated in human skin cells ( 29 ).…”
Section: Cutaneous Pathway For Melatonin Synthesismentioning
confidence: 99%
“…Physiologically, however, EPI and NE could be derived from other sources. Epidermal keratinocytes and melanocytes are capable of producing catecholamines (51) and EPI of adrenomedullary origin may reach skin cells as a hormone. Thus, the true physiological roles of ARs on LC and their function in states of sympathetic arousal remain to be elucidated.…”
Section: Figure 5 Intradermal Injection Of Epi Inhibits Chs Inductionmentioning
confidence: 99%
“…Interestingly, it has been shown that keratinocytes are capable of producing epinephrine [28,29], an endogenous adrenergic agonist with selectivity for the beta2AR, and basal layer keratinocytes produce higher levels of epinephrine than suprabasal keratinocytes [29]. Thus, it has been proposed that epinephrine activates keratinocyte beta2AR to modulate calcium influx and begin the differentiation cascade crucial to the native architecture of the epidermis [29]. The beta2AR desensitizes upon repeated activation through several mechanisms, including downregulation of the number of beta2AR receptors (reviewed in [30,31]).…”
mentioning
confidence: 99%